p5_6 Living on a prayer - Cox, Tom; Penn Fernandez, Keaton; Mead, Lara; Seagrave, Joshua (Physics Special Topics, 2020)
The big hit "livin' on a prayer" by Bon Jovi is still a popular song to this day, but when it comes to the physics of "living on a prayer", what does it take? When interpreting this phrase, a prayer can be said by an individual person at a normal speaking volume of 60 dB. It was found that it would require 41,000 people to produce enough sound pressure to levitate a 70kg man we will call Dave. For the least amount of people, it was found that 37 people would have to scream at 121 dB to be able to levitate Dave. For both cases this is assuming no pressure loss over distance.